2015
DOI: 10.1177/0308518x15597128
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational effects of parental wealth on children's housing wealth

Abstract: Past research has shown a close association of housing characteristics between generations. Previous evidence on the similarity of homeownership and housing value between parents and children reflects that inheritances and intergenerational wealth transfers play important roles in reinforcing and extending wealth inequality across generations. The purpose of this study is to examine how housing wealth and the timing of initial homeownership are affected by different characteristics of adult children and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Primarily, this derives from the fact that such parents have accumulated economic resources over their own life course (Mulder & Smits, 1999), where housing property is also often the most efficient or tax effective means of transmission. Secondly, homeownership has also proven to have a socialization effect, with the children of property owners predisposed to homeownership preferences themselves (see Henretta, 1984;Lersch & Luijkx, 2015;Lux et al, 2016;Ma & Kang, 2015). A third transmission effect is mediated through geographical proximity, with in-kind support, the transfer of property rights, land or entire dwellings more frequently provided where parents and children stay closer to each other.…”
Section: Housing and The Generational Contractmentioning
confidence: 99%
“…Primarily, this derives from the fact that such parents have accumulated economic resources over their own life course (Mulder & Smits, 1999), where housing property is also often the most efficient or tax effective means of transmission. Secondly, homeownership has also proven to have a socialization effect, with the children of property owners predisposed to homeownership preferences themselves (see Henretta, 1984;Lersch & Luijkx, 2015;Lux et al, 2016;Ma & Kang, 2015). A third transmission effect is mediated through geographical proximity, with in-kind support, the transfer of property rights, land or entire dwellings more frequently provided where parents and children stay closer to each other.…”
Section: Housing and The Generational Contractmentioning
confidence: 99%
“…In the UK, Udagawa and Sanderson (2017) revealed that first-time home buyers with parental support were 4.6 years younger than those without parental support. Similarly, Ma and Kang (2015) found that adult children whose parents are wealthy are more likely to transit quickly to homeownership in Korea. The extent of parental impact varies in different time periods.…”
Section: Literature Reviewmentioning
confidence: 88%
“…There is increasing evidence in Australia and internationally that parents represent an important source of finance for the purchase of owner-occupied housing. Rising house prices across major industrialised economies appear to have been both an enabler and cause of this development (Ma and Kang 2015;Scanlon, Blanc et al 2019). As house prices have increased, this has led to substantial increases in the housing wealth of existing home owners -especially older home owners-and accentuated the financing constraints faced by those wishing to transition into owner-occupation.…”
Section: The Contemporary Challenge Of Financing First-home Ownershipmentioning
confidence: 99%